Optimalisasi Peran Orang Tua dalam Mengembangkan Kreativitas Anak melalui Aktivitas Edukatif Keluarga untuk Mendukung Tujuan Pembangunan Berkelanjutan (SDGs) - Maria Melani Ika Susanti (Pusat Riset dan Inovasi Nasional, 2026)
Parents have a very important in supporting the growth and development of children's creativity from early age. This workshop is organized of community service to to aim of: (1) raising parents’ awareness in developing children's creativity through family educational activities; (2) adding references and inspirations for home educational activities; and (3) increasing family awareness to participate achieving the Sustainable Development Goals (SDGs), particularly in the aspects of Education and Human Development. The activity was held in Sungkur, RW 5, Klaten and attended by 17 PKK caretaker. The methods used informative lectures, participatory discussions, question-and-answer sessions, demonstrations of educational activities, and lived practice. The result showed big enthusiasm from the participants during the session, active discussions, and able to implement the educational family activities. This activity enhancing parents’ literacy about the importance of children's creativity in the context of sustainable development, which is incorporated into the SDGs at the village level.